Estudio de pre factibilidad para el montaje del laboratorio de caracterización de hidrocarburos no convencionales para el sector dowstream de la compañía SGS Colombia S.A. (2015)
This work of degree presents the prefeasibility of the assembly of a laboratory for the characterization of unconventional hydrocarbons; This document gathers all the information, analysis, structures and recommendations given for the success of the pre-feasibility and subsequent execution of the project.